Conditions for Oscillation of a Neutral Differential Equation. (14th June 2010) - Yan, Weiping; Yan, Jurang
Abstract : For a neutral differential equation with positive and changeable sign coefficients[ x ( t ) − a ( t ) x ( δ ( t ) ) ] ′ + p ( t ) F ( x ( τ ( t ) ) ) − q ( t ) G ( x ( σ ( t ) ) ) = 0, oscillation criteria are established, where q ( t ) is not required as nonnegative. Several new results are obtained.